Análise dos efeitos das taxas de câmbio, de juros e da renda mundial sobre as exportações brasileiras de mel natural - Oliveira, Ana Cláudia Sampaio de (2013)
The exchange rate, interest rate and world income are some of the most important variables of an economy, because in addition to mediate commercial and financial relations of a country with the rest of the world, can serve as an incentive for investment in the productive sector generating direct impact on exports. Thus, the present study proposes to test the possible existence of a long-term relationship, and the degree of influence of variables exchange rate, interest rate and world income on the export performance of Brazilian honey in the period the years 2000 and 2011. The empirical strategy adopted in this time series analysis was the use of a VAR model more complete model called vector error correction (VECM). This model is of economic significance, considering that, given the common dynamic in their data components have short term and long term. The results showed, from the analysis of long-term relationship, the variables exchange rate, interest rate and world income are extremely relevant to explain the oscillations occurred over time in the dependent variable export of honey. As for short-term analysis demonstrated that there is some lag time for imbalances occurring in the short term will be corrected in the long run. The same results also could be seen from the graphs of the impulse response functions and the reports generated in the decomposition process of the error variance. The relevance of factors that could cause structural breaks in the model, it was found that only the shock on the exchange rate, after the uncertainties of the electoral process in Brazil in 2002, and not the shock on income from the global economic and financial crisis in 2008/2009, was significant justifying the inclusion of a dummy in the model analysis. This model is of economic significance, considering that, given the common dynamic in their data components have short term and long term.